WHY DID THEY NEED TO COME NOW? COVID-19 CRISIS STRAINS RELATIONSHIPS WITH RETURNING AND VISITING COMPATRIOTS - Mieriņa, Inta; Reine, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
One of the first areas severely hit by the Covid-19 pandemic was international travel. In March/April, with commercial flights coming to a near halt, the governments were struggling to help their stranded citizens to return home. Extra flights and ferry trips were organised, and the opportunity to return was used by many emigrants worried about the uncertainty and the possible future development of the pandemic. This paper containing both data collected through survey and in-depth interviews with people aged 50+ in Latvia, is the first to explore the reactions of the society to repatriation policy implemented by the government of Latvia, and to explore how the Covid-19 situation has affected the attitudes towards return migrants in general. Importantly, it demonstrates how education moderates these attitudes. The results show that most of the population consider returning migrants as a significant source of infections, and many had doubts if they follow self-isolation and other rules responsibly. Those with the higher education were in general more supportive of the repatriation policy demonstrating the importance of education and explaining difficult decisions in order to reduce tension and fear.